2017
DOI: 10.15195/v4.a22
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Broken Windows: The Role of Neighborhood and Individual Characteristics in Reaction to Disorder Cues

Abstract: Using Turkey's 2013 Demographic and Health Survey, I find that among married women, having a single child as opposed to no children is associated with an approximately five-percentagepoint increase in the likelihood of religious veiling. Furthermore, the likelihood of religious veiling increases as the number of a woman's children increases. Robustness checks show that these associations are rather stable across the Muslim world. In addition, I use the sex of a woman's first child as a natural experiment and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This criticism has been partially addressed by attempts to replicate Keizer et al's (2008) results in different settings. Volker (2017) attempted to replicate Keizer et al's (2008) mailbox letter theft experiment in the identical neighborhood as the original study and failed to find significant effects. In their follow-up, Keizer et al (2011) found the effect of disorder on norm violation stronger in the presence of a sign prohibiting the form of disorder present; however, Wicherts & Bakker (2014) offered similar criticisms to those leveled at the first study.…”
Section: Review Of Experimental Studiesmentioning
confidence: 97%
“…This criticism has been partially addressed by attempts to replicate Keizer et al's (2008) results in different settings. Volker (2017) attempted to replicate Keizer et al's (2008) mailbox letter theft experiment in the identical neighborhood as the original study and failed to find significant effects. In their follow-up, Keizer et al (2011) found the effect of disorder on norm violation stronger in the presence of a sign prohibiting the form of disorder present; however, Wicherts & Bakker (2014) offered similar criticisms to those leveled at the first study.…”
Section: Review Of Experimental Studiesmentioning
confidence: 97%
“…The elderly might rely on their immediate surroundings more so than younger people who are relatively mobile and physically fit to spend their leisure time outside of the neighborhood. Married individuals-especially those with young children-might be more engaged with others in their neighborhood, because they are involved in their children's kindergarten, spend time on local playgrounds, or are generally motivated to create a safe environment for their children (Volker, 2017). Members of groups that are more likely to spend time in the neighborhood thus have a disproportionately larger chance of meeting and forming ties with each other.…”
Section: Conditional Neighborhood Effectsmentioning
confidence: 99%
“…However, the perception of crime was not (as expected) substantially linked to a particular group/class (e.g., youth) in the society. The direct impact of perceived societal dysfunction on expectations of crime was the most decisive influence in any model [44].…”
Section: Literature Reviewmentioning
confidence: 97%